2019
DOI: 10.1111/jdv.15475
|View full text |Cite
|
Sign up to set email alerts
|

Defining and measuring ‘eczema control’: an international qualitative study to explore the views of those living with and treating atopic eczema

Abstract: Background Atopic eczema (also known as eczema) is a chronic, inflammatory skin condition that often afflicts patients’ health and well‐being. The Harmonising Outcome Measures for Eczema ( HOME ) initiative recommends that ‘long‐term control of eczema’ is measured in all clinical trials 3 months or longer in duration. However, little has been published on what eczema control means to those living with or treating atopic eczema. Objectives To (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 17 publications
0
29
0
Order By: Relevance
“…and K.S.T. through synthesizing findings from an international qualitative study, an international patient survey and a systematic literature review relating to the construct of interest.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…and K.S.T. through synthesizing findings from an international qualitative study, an international patient survey and a systematic literature review relating to the construct of interest.…”
Section: Methodsmentioning
confidence: 99%
“…Experiences of eczema control were mapped onto the theoretical framework used in previous concept elicitation studies . L.M.H.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of these outcome measures, however, are time consuming and involve calculations only used within a clinical trial setting. We aimed to assess disease control in adults with moderate-to-severe AD who had been enrolled in the phase 3 CHRONOS study [ 2 ] using a simple and pragmatic patient-reported outcome: the number of well-controlled weeks [ 3 5 ] ( Trial Registration: ClinicalTrials.gov Identifier: NCT02260986).…”
Section: Digital Featuresmentioning
confidence: 99%
“…12 weeks), is recommended 32 . Long‐term control scores for use in clinical trials have recently been developed by international teams 33 …”
Section: Introduction and Definitionsmentioning
confidence: 99%